Pinkalicious - Kann, Victoria; Kann, Elizabeth (New York : HarperCollins, 2006)
A little girl who is obsessed with the color pink eats so many pink cupcakes that she herself turns pink.
Keywords: Food habits -- Fiction; Pink -- Fiction; Color -- Fiction